2010
DOI: 10.1080/02705060.2010.9664414
|View full text |Cite
|
Sign up to set email alerts
|

Reversed Diel Horizontal Migration of Fish: Turbidity Versus Plant Structural Complexity as Refuge

Abstract: Diel horizontal migration (DHM) by small perch (PercaJ2~iatili.s) between the littoral vegetation zone and open water was studied in the eutrophic Kirkkojtirvi basin (southern Finland). Small perch showed reversed DHM by occupying the open water area during daylight and moving into the littoral zone at dusk. They avoided the vegetation zone during daylight because water clarity among the plants was much higher than in the open water, which was attributed to the reductive effect of macrophytes on sediment resus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Macrophyte cover can reduce fish–prey encounter rates by adding physical barriers (Clemente et al, 2019; Meerhoff et al, 2007), whereas turbidity influences the reaction distance between fish and their prey by its negative impact on visibility (Snickars et al, 2004). However, the effect of increased turbidity on predation is supposed to be stronger than the effect of macrophyte cover (Carter et al, 2010; Pekcan‐Hekim et al, 2010); thus, when visibility is as reduced as observed in the more eutrophic lakes, predators may have switched to other means of finding prey or to foraging elsewhere (Figueiredo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophyte cover can reduce fish–prey encounter rates by adding physical barriers (Clemente et al, 2019; Meerhoff et al, 2007), whereas turbidity influences the reaction distance between fish and their prey by its negative impact on visibility (Snickars et al, 2004). However, the effect of increased turbidity on predation is supposed to be stronger than the effect of macrophyte cover (Carter et al, 2010; Pekcan‐Hekim et al, 2010); thus, when visibility is as reduced as observed in the more eutrophic lakes, predators may have switched to other means of finding prey or to foraging elsewhere (Figueiredo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of increased turbidity on predation is supposed to be stronger than the effect of macrophyte cover (Carter et al, 2010;Pekcan-Hekim et al, 2010); thus, when visibility is as reduced as observed in the more eutrophic lakes, predators may have switched to other means of finding prey or to foraging elsewhere (Figueiredo et al, 2013).…”
Section: Relationships Between Fish Attributes and Chla Concentrationmentioning
confidence: 99%
“…Interacting effects of habitat complexity and food web structure. Interestingly, habitat complexity interacts with lake characteristics such as water transparency (Snickars et al, 2004;Pekcan-Hekim et al, 2010) and trophic web characteristics. Rennie & Jackson (2005) demonstrated that small-scale variation in littoral microhabitat complexity shapes patterns of macroinvertebrate distribution but also that such effects were systematically different in the presence or absence of fish (i.e., greater complexity promoted higher density of invertebrates only in the presence of fish), suggesting that habitat complexity effects are at least partly mediated through top-down mechanisms.…”
Section: Future Directionsmentioning
confidence: 99%
“…Distribution and abundance of juvenile fishes is therefore usually positively correlated with the presence of aquatic plants (Comeau & Boisclair, 1998; Gaudreau & Boisclair, 1998; Jůza et al, 2018). Nonetheless, aquatic plants can provide safety only to a certain limit that depends on water turbidity (Pekcan‐Hekim et al, 2010), abundance of plant cover and presence and type of predators (Savino & Stein, 1989; Snickars et al, 2004). In high plant densities, juvenile fish can be safe from predators accustomed to hunting in open water but not so from ambush predators capable of manoeuvring in dense vegetation (Jacobsen & Perrow, 1998).…”
Section: Introductionmentioning
confidence: 99%